Efektivitas Video Pembelajaran dalam Meningkatkan Motivasi dan Hasil Belajar Siswa: Systematic Literature Review 2020–2025 - Rochimansyah Rochimansyah; Ana Sofiyatul Azizah; Ristiyani Ristiyani; Janatun Nurani; Herlina Setyowati (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2026)
Video has become a familiar learning medium because it combines sound, images, movement, and narrative in a form that is close to students’ everyday digital experiences. This study aims to synthesize the reported effects of video-based learning on learning motivation and learning outcomes in Indonesian educational contexts. A qualitative literature-study approach was used by reviewing publications indexed through Google Scholar for the 2020–2025 period. The source manuscript records an initial search of 1,870 items, a refined set of 56 publications, and 14 articles selected as the main body of analysis. The reviewed studies cover different educational levels and subjects, including Javanese language, Indonesian language, English, science, civics, phonology, and distance learning. Across the studies, video-based learning was generally associated with stronger attention, interest, active participation, and enthusiasm, while learning outcomes improved through higher average scores, increased mastery, and better performance compared with conventional instruction. Several studies also note limitations related to internet access, teacher preparation time, and uneven student participation. These findings suggest that video is most beneficial when used as a purposeful, accessible, and context-sensitive learning aid rather than as a substitute for meaningful teacher–student interaction.